Shaping Teenagers' Moral in the Digital Era: Islamic Education Perspective - Erni Yusnita; Andika Eko Prasetiyo; Uswatun Hasanah; Era Octafiona; Zahra Rahmatika (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2023)
One of the elements contributing to teenagers' moral deterioration is technological advancements in the digital era that are not aligned with their moral progress. This study aims to discover the moral issues of teenagers in the digital age, the concept of morality in Islam, and moral teaching from the perspective of Islamic education. This study employed library research with a descriptive-analytic approach. The study findings indicate that the sophistication of digital technology has negative consequences for teenagers, pushing them further away from religious ideals. The purpose of moral education in Islamic education for teenagers is to live according to Allah's commands and carry out their duties as servants of Allah and His representatives on earth. As a result, Islamic education is inextricably linked to efforts to instill Islamic educational values, including moral values known as akhlak.